SYSTEMATIC LITERATURE REVIEW: IMPLEMENTASI PENDEKATAN PEMBELAJARAN DIFERENSIASI PROSES BERDASARKAN KEMAMPUAN AWAL DALAM PEMBELAJARAN MATEMATIKA - Yudiasa, I Gusti Ayu Agung Intan Ananda Suari; Mertasari, Ni Made Sri; Dewi, Putu Kartika; Ardana, I Made; Mahayukti, Gusti Ayu (De Fermat : Jurnal Pendidikan Matematika, 2026)
Differentiated learning is a key solution to addressing student diversity. However, the implementation of specific process strategies based on students’ initial ability in mathematics learning still requires systematic review. This study aims to analyze and synthesize the literature related to the implementation of process differentiation based on students’ initial ability in mathematics learning. The method used was a Systematic Literature Review (SLR) with three screening stages PRISMA: identification, screening, and eligibility. Data was collected through the Google Scholar database, covering publications from 2021 to 2026. From the initial search results of 204 articles, 14 final articles were selected that met the inclusion criteria, including articles indexed by Scopus and Sinta. The results indicate that the most effective implementation of process differentiation in mathematics is achieved through mapping initial ability as a basis for determining instructional strategies, such as the use of work examples for low-ability students and tiered exercises and practice. The literature synthesis concluded that adaptively adapting the learning process to the initial ability profile not only improves learning outcomes but also optimizes students’ critical thinking skills and positive attitudes toward mathematics.